Private life as a fundamental right and the interception of communications - Giler Mendoza, Magda (2020)
The convergence between technological development, political objectives, and economic interests causes the current world a notable tension to safeguard the privacy and intimacy of the person, recognized as fundamental rights, which condition the sufficient freedom and self-determination of the person. This text offers a conceptual analysis, to describe these rights in their current situation and in which aspects conflicts arise, which the Law has to resolve. For the social mindset, the violation of a person's intimate space is unacceptable, regardless of the context in which they are found. Moreover, there are various spheres in which it can occur: work, in activities within an organization, in obtaining evidence for trials, or in situations that interest public order. In Ecuador, the legal regime is configured by constitutional recognition and in various legal bodies: criminal, procedural, electronic commerce, and in the Communication Law, plus the corresponding regulatory development. Furthermore, there is a demanding international framework that binds our country. However, there is a fear of exercising the right to express one's own thoughts: the expression of opinions in areas reserved for general knowledge does not seem to have sufficient guarantees. The invasion of privacy on the internet, like on social media, is seen as a sufficient threat. The debate becomes necessary when, besides, it is opposed to the right to information. Following the conceptual contributions provided by the doctrine, the right to privacy in the face of interference by the political power and the media must be configured in its proper terms. This allows us to outline a conceptual framework with timely relevance for the consideration of privacy in the Ecuadorian legal regime.